Third Five Year Plan 1961-66 Municipal Corporation of Delhi - Planning Commission (Planning Commission, 1961)
In order to avoid the heavy congestion and also to quicken the movement of through traffic which does not have to stop at Delhi, construction of the Ring Road (about 17.5 miles long) has been taken up. As its name indicates this road encircles Delhi and New Delhi connecting these National Highways and the important town ships and colonies lying around New Delhi. Most of the work on this road has been done except the Road overbridges with its approaches across Delhi Gurgaon, Delhi Rohtak and Delhi Karnal Railway lines which are in progress and a bridge across the Najafgarh Jheel Drain which is under planning. These will be completed in the 1st year of the Third Five Year Plan.
Municipal Corporation of Delhi